(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Human milk is a complex fluid, which contains a number of constituents such as fats, proteins and vitamins, in addition to other compounds. These nutrients are needed for infant protection against infections and diseases. This study was undertaken to evaluate some physicochemical properties and biochemical constituents content of human milk samples (based on the gender of the breast feeding infant). This includes acidity, density and viscosity, as well as lactose, protein, calcium and magnesium contents. Results showed that the highest value of viscosity as well as the highest percentages of protein and acidity were recorded for human breast milk for a boy (2.212 cP, 1.237% and 0.02% respectively) while close values for density and other biochemical contents were recorded for both types of samples. However, only the change in viscosity was found to be significant (p˂0.05). Variations in some properties of human milk depending on the infant’ sex could be of benefit for developing infant formula taking infant’s gender into consideration.